Impact of empagliflozin on insulin needs in patients with heart failure and diabetes: An EMPEROR-Pooled analysis - Talha, Khawaja M.; Green, Jennifer; Filippatos, Gerasimos; Pocock, Stuart; Zannad, Faiez; Brückmann, Martina; Schueler, Elke; Ofstad, Anne Pernille; Ferreira, João Pedro; Anker, Stefan D.; Butler, Javed; Rosenstock, Julio; et al. (Diabetes, obesity and metabolism, 2024)
Abstract Aim To assess the effect of empagliflozin on patients with comorbid heart failure (HF) and diabetes with or without baseline insulin, and to study the impact of empagliflozin on insulin requirements over time. Materials and Methods We performed a post-hoc analysis of pooled patient-level data from two cardiovascular outcomes trials of empagliflozin in HF (EMPEROR-Reduced and EMPEROR-Preserved trials). We undertook a subgroup analysis stratified by baseline insulin use, including all patients with diabetes. The studied endpoints included the primary composite endpoint of first hospitalization for HF or cardiovascular death, rate of decline of estimated glomerular filtration rate, composite renal outcome and rates of sustained insulin initiation. Results Among 4794 patients with diabetes, 1333 (658 in empagliflozin, 675 in placebo) were using insulin at baseline. The treatment effect of empagliflozin on the primary endpoint was consistent irrespective of insulin use [no insulin, hazard ratio 0.74, 95% confidence interval (CI) 0.63-0.86; using insulin, hazard ratio 0.81, 95% CI 0.66-1.00, pinteraction?=?.49], as was the effect on the rate of decline of the estimated glomerular filtration rate (pinteraction?=?.75). There was no effect of empagliflozin on the composite renal outcome in patients using or not using insulin (pinteraction?=?.30). Among patients not using insulin at baseline, those randomized to empagliflozin initiated insulin less frequently throughout the follow-up period compared with those receiving placebo (2.6% vs. 3.8%, odds ratio 0.66, 95% CI 0.50-0.88). Conclusions Empagliflozin exerts a consistent benefit on cardiovascular outcomes and renal function decline, irrespective of baseline insulin use, and reduces the need for sustained insulin initiation in patients with HF and diabetes.